2022
DOI: 10.1002/1873-3468.14467
|View full text |Cite
|
Sign up to set email alerts
|

cAMP‐induced decrease in cell‐surface laminin receptor and cellular prion protein attenuates amyloid‐β uptake and amyloid‐β‐induced neuronal cell death

Abstract: Previous studies have shown that amyloid-b oligomers (AbO) bind with high affinity to cellular prion protein (PrP C ). The AbO-PrP C complex binds to cellsurface co-receptors, including the laminin receptor (67LR). Our current studies revealed that in Neuroscreen-1 cells, 67LR is the major co-receptor involved in the cellular uptake of AbO and AbΟ-induced cell death. Both pharmacological (dibutyryl-cAMP, forskolin and rolipram) and physiological (pituitary adenylate cyclase-activating polypeptide) cAMP-elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Previously we found 67LR distributed on the cell surface of NS-1 cells [36,50]. The current study found that t-RES-3-G activates the cAMP/PKA/Epac signaling pathways.…”
Section: Discussionsupporting
confidence: 63%
“…Previously we found 67LR distributed on the cell surface of NS-1 cells [36,50]. The current study found that t-RES-3-G activates the cAMP/PKA/Epac signaling pathways.…”
Section: Discussionsupporting
confidence: 63%